Reliability of a laboratory-based long sprint cycling test: applications of the smallest worthwhile changes in performance for repeated measures designs - Rogério Santos de Oliveira Cruz; Rafael Alves de Aguiar; Tiago Turnes; Felipe Domingos Lisbôa; João Antônio Gesser Raimundo; Fabrizio Caputo (Universidade Federal de Santa Catarina, 2018)
The aims of the present study were to assess the reliability of long sprint cycling performance in a group of recreationally trained cyclists and to provide thresholds for changes in performance for this particular group of subjects in repeated measures designs through a scale of magnitudes. Repeatability of mean power output during a 1-min cycling time trial was assessed in a group of 15 recreationally trained cyclists (26 ± 5, years, 176 ± 5 cm, 78 ± 8 kg). They were tested on separate days, approximately one week apart. The test and retest values for the whole group of cyclists were 7.0 ± 0.5 W/kg and 6.9 ± 0.6 W/kg (systematic change and 90% confidence limits of -1.0% ± 1.1%). Our results indicated good test-retest reproducibility (typical error of 1.8%, 90% confidence limits of 1.4% to 2.6%; intraclass correlation coefficient of 0.96, confidence limits of 0.91 to 0.99), but suggested a reduction of mean power for the "slower" subjects on retest (-2.0%, 90% confidence limits of ±1.8%). If not monitored, this systematic decrease could interfere in results of studies utilizing groups with similar performance levels, particularly investigating strategies to improve performance in sprint cycling exercises around 1 min. The thresholds for moderate, large, very large and extremely large effects for mean power output on long sprint cycling performance are about 0.4%, 1.3%, 2.3%, 3.6%, and 5.8%, respectively.